(untitled) (Medical Forum Monthly, 2024)
Objective: To determine the extent and feto maternal factors contributing to perinatal Mortality. Study Design: A prospective review study. Place and Duration of Study: This study was Gynecological and Neonatal Intensive care units of BMCH, Quetta from January 2006 to December 2011 Patients and Methods: A prospective review of all still births from 24 weeks of pregnancy and on words and neonatal deaths within first seven days of life either in obstetric ward or neonatal nursery was done. The details of each mother and new born were recorded on standardized proforma. Results: The perinatal mortality rate was 99/1000during last 6 years, 102/1000 in 2006, 97/1000 in 2011 Most common maternal cause for perinatal morality was hypertensive disorders of pregnancy 26%, then antepartum hemorrhage 23.8%, birth asphyxia 23%, Congenital anomaly contributed 5.3%, unexplained 7% of all. Conclusion: Perinatal mortality is a major health problem caused by poor maternal health, lack of antenatal visits, multiparity, prematurity and infections of both mother and new born. Antenatal care, birth spacing, proper referral and standardized management during labour and in nursery can reduce the perinatal mortality.